(untitled) (Health Education in Practice: Journal of Research for Professional Learning, 2020)
Purpose: This study aims to offer guidance to lecturers and undergraduate midwifery students in using reflective practice and to offer a roadmap for academic staff accompanying undergraduate midwifery students on international clinical placements. Design: Drawing on reflection within the Constructivist Theory, the Gibbs Reflective Cycle (GRC) provides opportunities to review experiences and share new knowledge by working through five stages—feelings, evaluation, analysis, conclusion and action plan. Findings: The reflections of the midwifery students in this study provide insight into expectations prior to leaving for international placement, practical aspects of what local knowledge is beneficial, necessary teaching and learning strategies and the students’ cultural awareness growth. Implications: The analysis and a reflective approach have wider implications for universities seeking to improve preparations when embarking on an international clinical placement. It can also inform practices that utilise reflection as an impetus to shape midwifery students to be more receptive to global health care issues.